Magnetic Fem (M = Ag, Co, Cu, and Ni) Nanocrystals as Electrocatalysts for Hydrogen Evolution Reaction - Casagrande-Denardin, J (Elsevier Ltd, 2022)
Iron-based magnetic nanocrystals (FeM@OAm, M = Ag, Co, Cu, and Ni; OAm = oleylamine) electrocatalysts have been successfully synthesized via oleylamine reduction of metal salts method. FeCo is arranged in a body-centered cubic (bcc) unit cell, while FeNi, FeAg, and FeCu are in a face-centered cubic (fcc) structure. All the samples have different morphologies with a diameter average size varying of 6.4 ± 1.0 to 21.7 ± 5.1 nm, depending on the bimetallic composition. The samples have ferrimagnetic behavior with low coercive field and high saturation magnetization values at room temperature. Furthermore, it has been shown that FeAg fits better in the solid solution category. Among heterogeneous electrocatalysts synthesized, FeCo nanocrystals show lower overpotential (−564 mV) in comparison to FeAg (−584 mV), FeNi (−666 mV), and FeCu (−591 mV). The Tafel plots showed that the hydrogen evolution reaction (HER) activity for electrocatalyst following a mixed of Volmer−Heyrovsky reaction mechanism, suggests that reaction Volmer is the determining step. In addition, all electrocatalysts showed stability in tests of continuous operations showing only low potential variation. The EIS study shows system characterized by two time-constant, both of them may related to the kinetics of the HER related to the charge transfer kinetics and the hydrogen adsorption. Thus, these materials are sustainable for electrochemical water splitting since showed acceptable electrocatalytic performance toward HER in alkaline media with excellent physical stability and abundance of active sites for HER. © 2022 Elsevier Ltd